Using a vision cognitive algorithm to schedule virtual machines - Zhao, Jiaqi; Mhedheb, Yousri; Tao, Jie; Jrad, Foued; Liu, Qinghuai; Streit, Achim (Zielona Góra: Uniwersytet Zielonogórski)
Scheduling virtual machines is a major research topic for cloud computing, because it directly influences the performance, the operation cost and the quality of services. A large cloud center is normally equipped with several hundred thousand physical machines. The mission of the scheduler is to select the best one to host a virtual machine. This is an NP-hard global optimization problem with grand challenges for researchers.
Keywords: cloud computing; vision cognitive algorithm; VM scheduling; simulation